2013
DOI: 10.1128/iai.00275-13
|View full text |Cite
|
Sign up to set email alerts
|

Importance of PdpC, IglC, IglI, and IglG for Modulation of a Host Cell Death Pathway Induced by Francisella tularensis

Abstract: Modulation of host cell death pathways appears to be a prerequisite for the successful lifestyles of many intracellular pathogens. The facultative intracellular bacterium Francisella tularensis is highly pathogenic, and effective proliferation in the macrophage cytosol leading to host cell death is a requirement for its virulence. To better understand the prerequisites of this cell death, macrophages were infected with the F. tularensis live vaccine strain (LVS), and the effects were compared to those resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
(98 reference statements)
3
21
0
Order By: Relevance
“…S2 in the supplemental material), whereas the ⌬iglA and ⌬iglC mutants showed no growth, which was in agreement with previously published data (27,55). Significant growth of LVS and the ⌬iglG and ⌬pdpE mutants was observed also in BMDM, whereas none of the other three mutants showed any replication (see Fig.…”
Section: Requirement Of Fpi Proteins For Replication After Phagocyticsupporting
confidence: 82%
See 1 more Smart Citation
“…S2 in the supplemental material), whereas the ⌬iglA and ⌬iglC mutants showed no growth, which was in agreement with previously published data (27,55). Significant growth of LVS and the ⌬iglG and ⌬pdpE mutants was observed also in BMDM, whereas none of the other three mutants showed any replication (see Fig.…”
Section: Requirement Of Fpi Proteins For Replication After Phagocyticsupporting
confidence: 82%
“…The ⌬iglG mutant replicates efficiently in the J774 macrophage cell line and in primary macrophages, whereas the ⌬iglI mutant replicates only in the former cell type (27). We previously noted, however, that the latter two mutants induced much less prominent host cell cytopathogenic effects than did the parental strain, suggesting a requirement for the encoded proteins in modulating the host cell death pathway induced by F. tularensis (27,55). In contrast, the ⌬pdpE mutant is one of the few FPI mutants that exhibits wildtype phenotypes with regard to replication and cytopathogenicity in monocytic cells (27).…”
Section: Requirement Of Fpi Proteins For Replication After Phagocyticmentioning
confidence: 96%
“…For example, whereas both LVS iglI and iglG mutants showed essentially wild-type growth in J774 macrophages, only the iglG mutant was proficient for growth in peritoneal exudates and BMMs (22). Differences in intracellular replication and induction of host cell death pathways were also observed following infection of J774 macrophages with pdpC, iglC, iglG, or iglI mutants of LVS (56). Consistent with this result, Long et al found that while Schu S4 iglI and IglJ were essential for phagosomal escape and alteration of endosomal trafficking, a mutant lacking pdpC was only partially defective in this regard (30).…”
Section: Discussionmentioning
confidence: 90%
“…Although no effector functions have been assigned to the proteins of the FPI, many of those studied so far have been found to be essential for phagosomal escape and intracytosolic replication of the pathogen, as well as modulation of the host response (14,(27)(28)(29)(30)(31)(32)(33)(34)(35). Several recent publications have addressed the role of PdpC by investigating the phenotypes of specific pdpC mutants or a spontaneous mutant (14,(35)(36)(37). Mutants derived from strain LVS or SCHU S4 have both demonstrated unique phenotypes, since they showed incomplete phagosomal escape, growth in only a small subset of macrophages, intermediate cytopathogenic effects, and marked attenuation in vivo but modulation of the macrophage inflammatory response similar to that of the parental strains (14,35,36).…”
mentioning
confidence: 99%
“…Several recent publications have addressed the role of PdpC by investigating the phenotypes of specific pdpC mutants or a spontaneous mutant (14,(35)(36)(37). Mutants derived from strain LVS or SCHU S4 have both demonstrated unique phenotypes, since they showed incomplete phagosomal escape, growth in only a small subset of macrophages, intermediate cytopathogenic effects, and marked attenuation in vivo but modulation of the macrophage inflammatory response similar to that of the parental strains (14,35,36). Very recently, a spontaneously attenuated SCHU S4 mutant was described (37).…”
mentioning
confidence: 99%